Perspektif Kekuatan dalam Pekerjaan Sosial - -, Ishartono; Raharjo, Santoso Tri (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2016)
A lot of social issues generally approached the issue of problem-based approach (PBA) with a variety of other derivative terms, namely medical model, the deficit approach, or a more traditional approach. Problem-based approach to focus more on weaknesses in the client’s self that causes problems, both at the micro, mezzo and macro levels. PBA is less attention to the potentials, aspirations, hopes and potential sources residing on the client and the client environment. Strength-based approach (strength perspective) as a perspective emerged in response to the previous approach. This approach started to pay attention to the potential, aspirations, expectations and resources that can be utilized within the framework of solving social problems. For the social work profession, this perspective provides a new angle to look at and address the social problems facing clients.Keywords: Problem Based Approach, Strength Perspective, Social Work